Electrical Properties of Starch/Chitosan-Nh4no3 Polymer Electrolyte - Azwani Sofia Ahmad Khiar; A.K. Arof (World Academy of Science, Engineering and Technology, 2024)
Starch/chitosan blend have been prepared via the solution casting technique. Ionic conductivity for the system was conducted over a wide range of frequency between 50 Hz-1 MHz and at temperatures between 303 K and 373 K. Sample with 35 wt% of NH4NO3 shows the highest conductivity of 3.89 ± 0.79 x 10-5 Scm-1 at room temperature. Conductivity-temperature relationship suggests that samples are Arrhenian. Power law exponent was obtained through dielectric loss variation and the trend suggests that the conduction mechanism of the ions can be represented by the correlated barrier hopping (CBH) model.